2020
DOI: 10.1101/2020.08.20.248302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Noninvasive Approach to Optogenetics Using Focused Ultrasound Blood Brain Barrier Disruption for the Delivery of Radioluminescent Particles

Abstract: Optogenetics, the genetic incorporation of light-sensitive proteins such as Channelrhodopsin-2 (ChR2) into target mammalian neurons, has enabled activation, silencing, and receptor subtype specific neuromodulation with high spatiotemporal resolution. However, the essential components of the ontogenetic system require invasive procedures with very few non-invasive alternatives preventing its use as a translational tool. The implantation of light emitting fibers deep within brain structures is both technically d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 34 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Radioluminescent nanoparticles have been shown to persist in brain tissue for at least 72 h after injection [54], enabling repeated experiments over multiple days. Radioluminescent nanoparticles can also be delivered into the brain using focused ultrasound to open the blood brain barrier [22], avoiding the damage of intracranial injection. X-ray activation of RLPs is therefore a potentially viable method for noninvasive optogenetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radioluminescent nanoparticles have been shown to persist in brain tissue for at least 72 h after injection [54], enabling repeated experiments over multiple days. Radioluminescent nanoparticles can also be delivered into the brain using focused ultrasound to open the blood brain barrier [22], avoiding the damage of intracranial injection. X-ray activation of RLPs is therefore a potentially viable method for noninvasive optogenetics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, LSO:Ce is nonhygroscopic, biologically inert, and can be synthesized at the nanoscale level [76,77]. While we used microparticles in this study, LSO:Ce nanoparticles could be used to increase their likelihood of passing through the blood-brain barrier, especially if used together with focused ultrasound to increase BBB permeability [22]. We previously demonstrated that LSO:Ce microparticles are non-toxic to neurons and had very minor effects on synaptic transmission [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rich et al (2020) reported successful non-invasive delivery of light-emitting radio luminescent X-ray sensitive particles (RLPs) to the hippocampus of rats using magnetic resonance imaging (MRI)-guided focused ultrasound (FUS). Crucially, MRI-guided FUS can be used to deliver both RLPs and viral vectors for light-sensitive channel expression as demonstrated by Wang et al (2017).…”
Section: Reply To Objections About Potential Therapeutic Applicabilit...mentioning
confidence: 99%
“…In contrast, findings of recent years have shown that the prospect of providing measures to selectively deactivate the targeted memory can be actually realized with the use of an emerging MMT-optogenetics [35][36][37]. Although making optogenetic system operable to control neural activity underlying the memory still involves invasive manipulations, i.e., inserting opsin genes via viral infection and implanting optical fibers, less invasive optogenetic-systems are currently under development (see [38][39][40][41][42] for recent advancements in making optogenetics less or even non-invasive). While it may take years to make optogenetics or optogeneticlike technology a therapeutic memory-modifying measure, 2 if ever to be realized, 3 the fact that MMT has been shown to be effective in deactivating specific memories makes it timely and important to consider potential philosophical 4…”
Section: Introductionmentioning
confidence: 99%